Intravenous fosfomycin—back to the future. Systematic review and meta-analysis of the clinical literature. (June 2017) - Grabein, B.; Graninger, W.; Rodríguez Baño, J.; Dinh, A.; Liesenfeld, D.B.
Abstract: Objectives: We conducted a systematic review and meta-analysis to summarize the clinical evidence and usage patterns of intravenous fosfomycin from its development to the present time. Methods: PubMed, the Cochrane Library and local journals were searched for relevant studies reporting aggregated data of intravenous fosfomycin use in adults and children, with no restrictions regarding study design. Single case reports were excluded. Data were systematically abstracted for all included studies. Clinical and microbiological efficacy from randomized controlled and comparative observational studies were synthesized using meta-analysis to calculate pooled effect sizes. Results: In all, 128 studies on intravenous fosfomycin in 5527 patients were evaluated. Fosfomycin was predominantly used for sepsis/bacteraemia, urinary tract, respiratory tract, bone and joint, and central nervous system infections. No difference in clinical (OR 1.44, 95% CI 0.96–2.15) or microbiological (OR 1.28, 95% CI 0.82–2.01) efficacy between fosfomycin and other antibiotics was observed in comparative trials. The pooled estimate for resistance development during fosfomycin monotherapy was 3.4% (95% CI 1.8%–5.1%). Fosfomycin showed a favourable safety profile, with generally mild adverse events not requiring discontinuation of treatment. Included studies explored intravenous fosfomycin as an anti-staphylococcal agent in monotherapy and combination therapy, whereas studies from 1990 focused on combination therapy (fosfoymcin + β-lactams or aminoglycosides) for challenging infections frequently caused by multidrug-resistant organisms. Conclusion: Intravenous fosfomycin can play a vital role in the antibiotic armamentarium, given its long history of effective and safe use. However, well-designed randomized controlled trials are still desired.